From Risk to Readiness: A Cross-Sectional Study on Pre-Exposure Prophylaxis Willingness Among Migrant Men Who Have Sex With Men in Thailand - Kyaw, Pyae Phyo; Thepthien, Bang-on (The Journal of the Association of Nurses in AIDS Care, 2025)
HIV prevalence among migrants from neighboring countries in Thailand is reported to be up to four times higher than that of the general Thai population. Migrant men who have sex with men (MMSM) in Thailand face an increased risk of HIV due to limited health care access and insufficient targeted prevention programs. Our study explores the relationship between sexual risk behaviors and willingness to use preexposure prophylaxis (PrEP) among MMSM ages 18–59 years in Thailand. Using multimediation analysis with the PROCESS macro for SPSS, it examines whether PrEP-related attitudes, self-efficacy, and awareness mediate this relationship. Results indicate that attitudes and awareness significantly mediate the link between sexual risk behaviors and PrEP willingness, whereas self-efficacy does not have a notable indirect effect. The combined mediators (B = 0.106, 95% confidence interval [0.041–0.171]) explain the observed effect, highlighting the crucial role of attitudes and awareness in promoting PrEP adoption. These findings underscore the importance of developing interventions that enhance awareness and foster positive attitudes toward PrEP to optimize its implementation and uptake among sexually active MMSM.